The Effect of TENS and Ultrasound Diathermy on Osteoarthritis Patients in Physical Medicine and Rehabilitation Unit of Patut Patuh Patju Hospital, West Nusa Tenggara - Irawan Irawan; Tannia Rizkyka; Muhayani Muhayani; Gustin Fat’aah (Syntax Idea)
Osteoarthritis is generally recognized as a common musculoskeletal condition in Indonesia, characterized by the degeneration of joint cartilage and narrowing of the joint space. The form of therapy that can be given to knee OA patients is a combination of TENS therapy and ultrasound diathermy (USD). WOMAC is an index used to measure osteoarthritis patiens based on pain, stiffness, and physical function. Patut Patuh Patju General Hospital is the only hospital in West Lombok district where physical medicine and medical rehabilitation have recently been introduced. This research aims to determine the effects of administering TENS and ultra sound diathermy on OA patients in the physical medicine and rehabilitation unit of Patut Patuh Patju Hospital, a newly established district hospital in NTB, which has been operational for the past year. This type of research uses a pre-experimental design with a one group pretest-posttest method. Sampling was taken using a purposive sampling technique with a total sample of 30. The research population was knee osteoartritis patients undergoing physiotherapy treatment at the Medical Rehabilitation Unit of Patut Patuh Patju General Hospital. Data was collected using the WOMAC questionnaire before and after 6 until 8 times therapy. The distribution of research data was analyzed using the Shapiro-Wilk test. If the data distribution is normal, it is analyzed using the paired t-test, whereas if it is not normal, it is analyzed using the Wilcoxon test. The combination of TENS therapy and ultra sound diathermy results in improvement of WOMAC scores in knee osteoarthritis patients with p-value = 0.000 (p < 0.05).